The Chewing Habits on One Side of the Jaw and the Status of Dental and Oral Hygiene in Adolescents in Manado City: A Cross-sectional Study - Anneke Tahulending; Novarita M. Koch; Jeineke Ellen Ratuela; Jeana Lydia Maramis; Jeanne d’arc Zafera Adam; Oksfriani Jufri Sumampouw (Indonesian Journal of Public Health and Community Medicine, 2024)
Background: Overall body health is important, including dental and oral health which is part of body health. The habit of chewing food on one side is caused because the teeth on one side feel painful or uncomfortable when used to chew food or it can also be because it has become a habit. Oral hygiene can be measured based on the Simplified Oral Hygiene Index (OHI-S) measure. The purpose of this study is to measure the correlation between one-sided chewing habits and the dental and oral hygiene status of adolescents in Manado City. Method: This is a correlational research with a cross-sectional approach. This research was carried out in May-June 2023 at the Miftahul Jannah Mosque, North Titiwungen Village, Sario District, Manado City. The respondents in this study were 60 adolescents aged 12-17 years. The research variables were one-sided chewing habits and dental and oral hygiene. The research instruments are diagnostic tools, checklist sheets and OHI-S assessment formats. The data obtained were analyzed using the chi squared test. Results: The results showed that 39 respondents (65%) chewed using one side of the jaw. The average value of OHI-S was 2.4 and as many as 42 respondents (70%) had moderate criteria for dental and oral hygiene status. The test results when squared obtained a correlation value of 0.000 (< 0.05), this means that the habit of chewing on one side is significantly related to the status of dental and oral hygiene. Conclusion: It can be concluded that the habit of chewing one side of the jaw is related to the dental and oral hygiene status of adolescents in Manado City. Therefore, it is hoped that adolescents can get used to chewing on both sides of the jaw so that the dental and oral hygiene status of adolescents can be well maintained.